Evaluation of the early childhood health and family life education pilot curriculum for Jamaica - Faulkner, Doreen M. (2011)
Aims to obtain information about aspects of the usefulness of the curriculum objectives and content prior to preparing the guide for national implementation. Gives teachers suggested activities and questions to use in assessing students' knowledge on the four themes of the curriculum. Includes expectations of what the child should be able to do for each activity.